Exploring Learning Difficulties and Causal Factors in Javanese Scripts: Student and Teacher Perspectives in Indonesian High School - Nur Hanifah Insani; Yusuf Nur Kholiq (Jurnal Pemberdayaan Masyarakat, 2025)
Teaching Javanese script at the senior high school level still faces challenges from student limitations and pedagogical aspects. This study aims to explore the difficulties experienced by senior high school students in learning Javanese script and to identify the factors causing these difficulties from the perspectives of both students and teachers. This study employs a qualitative descriptive approach, with data collected through a questionnaire administered to 2.437 students and in-depth interviews with 14 Javanese language teachers. The data were analyzed through data condensation, data presentation, and drawing and verifying conclusions. The results of the study indicate that the main difficulties experienced by students include reading Javanese script sentences (72.9%), understanding Javanese vocabulary (71.3%), memorizing script forms (64.1%), identifying word divisions (59%), and distinguishing specific phonemes. The factors contributing to these difficulties include low literacy habits, minimal technology use, teaching methods unsuitable for the students' characteristics, limited learning resources, and inadequate learning feedback. This study offers novelty by formulating a contextual, technology-based learning strategy for the Javanese script that aligns with students’ characteristics. Its contribution lies in enriching the field of local language education and providing new directions for the development of more adaptive educational policies.